Exploratory Data Analysis on the Process of Determining the Relationship between Student Interest and Talent Variables - Elfaladonna, Febie (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
One of the determinants of a student's success in the future is the maximum management of interests and talents. To support the classification of interests and talents in schools, it can be done by using exploratory data analysis techniques.Exploratory data analysis (EDA) is one of the important stages in the data science cycle. The EDA process carried out on the dataset of elementary school students comes from the student interest and talent questionnaire filled out by parents. EDA processing in this study uses several python programming libraries. as for the purpose of the study is to find the relationship or relationship between items on the dependent variable and the independent variable. this feature will later be carried out on model building. The main methods used in the implementation of EDA are chi square and T-test.